Attitudes and environmental policies for the conservation of snakes and the prevention of snakebite accidents: An integrative review (Research, Society and Development, 2024)
According to the World Health Organization, the main accidents in the tropics are scorpions and poisonous snakes. These accidents can lead to serious clinical complications and possibly death. The aim of this study was to survey the knowledge produced in the Brazilian literature on environmental actions and policies aimed at conserving snakes and preventing snakebite accidents. The research was characterized as a descriptive study, of the integrative literature review type. Using the descriptor snake, 15 articles were found in the Latin American and Caribbean Literature in Health Sciences (LILACS) database. Of these, 9 were selected and 6 were excluded as they did not meet the research objective. With the descriptor ophidism, 7 articles were found, of which all were excluded due to repetition and/or for not meeting the research objective. A total of 9 articles were selected. Ophidian accidents continue to be an important cause of accidents in Brazil, and are therefore a public health problem with consequences that lead to weak and limited economic development in communities. Training rural populations and health personnel is important to avoid secondary complications from empirical treatment.